Asuhan keperawatan Pada Keluarga Ny.B Dengan Masalah Utama GOUT Pada Ny.B Di Desa Jagalan, Pabelan,Kartasura, Sukoharjo - Zakhiah, Nur Rochma Laily, H.M. Abi Muhlisin, SKM., M.Kep (2015)
Background: The high incidence of gout is caused by the high number of person who consume protein-rich(purine) foods and increasing number of gout incidence is associated with changes in dietary patternsand lifestyle.Increasing cases of obesity and metabolic syndrome cause uric acid levels increased due to inhibition of purine disposal. Based on the data from Community Health Center I of Kartasura, the number of gout patients in Kartasura area increased 23% in March-April 2015 which reached 48 cases. 3 of themwere old cases and the rest 45 cases were new cases. Objective: To determine the nursing care ofMrs.B family with major problemin uric acid (gout) to Mrs.B which includes assessment, diagnosis, intervention, implementation and evaluation. Results: After family nursing care for 3x30 minutesvisitations showed a reduced pain, increased knowledge of the family and family's acceptance on what the author taught. The family also could do it well. Conclusion: Cooperation between the health care team and patient/family is indispensable for the success of family nursing care, therapeutic communication can encourage patients and familyto be more cooperative, warm compresses can reduce the accumulation of purines in the joints and reduce pain and ROM activecan train the muscle strength back. Keywords: gout, pain, increased purine, ROM, Nursing care